Arthroscopic Debridement and Resection of a Bennett Lesion in a Collegiate Baseball Pitcher - Galvin J. Loughran MD; Ian Hollyer MD; Kevin Helenius MPA, PA-C, ATC; Michael Heffner MD; Michael T. Freehill MD (SAGE Publishing, 2024)
Background: Overhead throwing athletes are predisposed to ossification along the superior to inferior posterior glenoid rim, termed thrower's exostosis or a Bennett lesion. These lesions can result in posterior shoulder pain during throwing and decreased shoulder range of motion, and they can be associated with posterior labral tears and undersurface rotator cuff tears. In this video technique, we describe the arthroscopic debridement and resection of a symptomatic unstable Bennett lesion in a collegiate baseball pitcher who had unsuccessful nonoperative treatment. Indications: Currently, there is no standard treatment algorithm for Bennett lesions. Arthroscopic intervention is typically indicated in overhead throwers who have unsuccessful nonoperative protocols, including stretching of the posterior capsule, strengthening of the rotator cuff, and injections. Technique Description: In the lateral decubitus position, standard posterior viewing and anterior working arthroscopic portals are created followed by diagnostic arthroscopy. A high anterior accessory portal is created to view the posterior labrum and evaluate for tears. The location of the Bennett lesion is determined using a switching stick or probe. In this case, an accessory posterior viewing portal and capsulotomy are created under spinal needle visualization and a 70° scope is utilized for an improved view. Through the capsulotomy, a motorized shaver and radiofrequency wand is used to work along the posterior inferior glenoid neck to expose the lesion. Once the lesion is fully demarked, a hooded bur is utilized to debride the entirety of the lesion back to the smooth bony surface of the glenoid neck. After resection, the capsule is left open to avoid overtightening the posterior capsule in overhead throwing athletes. Results: Arthroscopic debridement and resection of a symptomatic Bennett lesion in a collegiate baseball pitcher allowed the patient to return to pain-free pitching at the same level of collegiate play the following season. Discussion/Conclusion: An unstable Bennett lesion can be a source of pain in the overhead throwing athlete. If nonoperative treatment modalities fail to resolve symptoms, arthroscopic debridement and excision of this lesion utilizing a posterior capsulotomy and accessory posterior viewing portal as described in this video technique is a safe and effective surgical option. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.